On the evolving and emitting quantum black holes and the scale independent black hole cosmology - Satya Seshavatharam, U.V; Lakshminarayana, S (International Journal of Advanced Astronomy, 2014)
Along with presently the believed black holes that are expected to be formed by gravitational collapse of a massive star, there may exist primordial evolving black holes. By absorbing the hidden vacuum energy primordial evolving black holes become massive. Planck mass can be considered as the basic mass of any black hole and can be called as the baby Planckion. Very high temperature of the baby Planckion is the only heat source for the evolving black holes or evolving Planckion’s decreasing temperature. Considering the current cosmic microwave back ground temperature as a quantum gravitational effect of the evolving primordial cosmic black hole, general theory of relativity and quantum mechanics can be combined into a ‘scale independent’ true unified model of quantum gravity. Considering cosmic black hole’s light speed rotation and galactic revolution, observed galactic rotational curves can be understood. In the past, decreasing high cosmic black hole temperature forced hydrogen atom to emit increasing photon energy resulting in the observed redshift. Aged super novae dimming may be due to the effect of past high cosmic black hole temperature. As cosmic time passes, decreasing current cosmic black hole temperature makes hydrogen atom to emit increased quanta of energy causing the future redshift. In future, with reference to the laboratory hydrogen atom, decreasing current cosmic temperature and measured rate of increase in emitted photon energy - true rate of future cosmic expansion can be understood. With reference to the decreasing current Hubble constant and decreasing current cosmic black hole temperature, true rate of future cosmic expansion can also be understood. Foundations of Quantum mechanics and General theory of relativity may be reviewed in this unified way. Keywords: Quantum Gravity, Evolving Black Holes, Geometric Horizon, Standard Cosmology, Black Hole Cosmology, CMBR Isotropy and Anisotropy, Redshift, Galactic Rotational Curves.